Cassava Brown Streak Disease response and association with agronomic traits in elite Nigerian cassava cultivars - Ano, C.U.; Ochwo-Ssemakula, Mildred; Ibanda, A.; Ozimati, A.; Gibson, P.; Onyeka, J.; Njoku, D.; Egesi, Chiedozie N.; Kawuki, R.S. (Frontiers Media, 2021)
Cassava mosaic geminiviruses (CMGs) and cassava brown streak viruses (CBSVs) cause the highest yield losses in cassava production in Africa. In particular, cassava brown streak disease (CBSD) is and continues to be a significant constraint to optimal cassava production in Eastern and Southern Africa. While CBSD has not been reported in West Africa, its recent rapid spread and damage to cassava productivity in Eastern, and Southern Africa is alarming. The aim of this study was to evaluate Nigerian cassava genotypes in order to determine their responses to CBSD, in the event that it invades Nigeria, the world’s largest cassava producer. The study gathered information on whether useful CBSD resistance alleles are present in the elite Nigerian cassava accessions. A total of 1,980 full-sib cassava seedlings from 106 families were assessed in the field at the seedling stage for a year. A subset of 569 clones were selected and assessed for another year at the clonal stage in Namulonge, central Uganda, a known hotspot for CBSD screening. Results indicated that foliar and root incidences and severities varied significantly (p ≤ 0.01, p ≤ 0.001) except for CBSD foliar incidence at 6 months (CBSD6i). Highest and lowest plot-based heritability estimates for CBSD were registered for CBSD root severity (CBSDrs) (0.71) and CBSD6i (0.5). Positive and highly significant correlations were noted between CBSD root incidence (CBSDri) and CBSDrs (r = 0.90∗∗∗). Significant positive correlations were also noted between CBSD foliar severity at 3 months (CBSD3s) and CBSD foliar incidence at 6 months (CBSD6i ) (r = 0.77∗∗∗), CBSD3s and CBSDrs (r = 0.35∗∗∗). Fresh root weight (FreshRW) negatively correlated with CBSDri and CBSDrs, respectively (r = −0.21∗∗∗ and r = −0.22∗∗∗). Similarly, CBSD3s correlated negatively with cassava mosaic disease severity at 3 (CMD3s) and 6 months (CMD6s), respectively (r = −0.25∗∗∗ and r = −0.21∗∗∗). Fifteen clones were selected using a non-weighted summation selection index for further screening. In conclusion, results revealed that the elite Nigerian accessions exhibited significant susceptibility to CBSD within 2 years of evaluation period. It is expected that this information will aid future breeding decisions for the improvement of CBSD resistance among the Nigerian cassava varieties.